Sociolinguists and their publics: Epistemological tension and disciplinary contestation over language in Catalonia. (27th October 2021) - Erdocia, Iker; Soler, Josep
Abstract: This article aims to investigate the relationship of sociolinguists with the publics in Catalonia and to disentangle the complex interrelationships among academics within the discipline. By examining material from mainstream media outlets and data from interviews with a selected number of sociolinguist scholars, we show how the public sphere is a site in which competing epistemological and disciplinary visions contest for discursive dominance in language‐in‐society matters, institutional authorization, and resources. Rather than seeing the engagement of sociolinguists with publics as a disinterested activity of knowledge dissemination and the provision of facts, we argue that the publics are better conceived as a terrain toward which sociolinguists direct institutional, disciplinary, and professional interests. Ultimately, our article contributes to a more encompassing understanding of ourselves as sociolinguists. Resum: Aquest article pretén investigar la relació entre sociolingüistes i l'esfera pública (que inclou l'audiència i diversos altres agents acadèmics) a Catalunya per entendre millor la complexitat de la interconnexió entre acadèmics en la disciplina. Partint de l'anàlisi de material publicat en mitjans de comunicació i d'entrevistes amb un grup de sociolingüistes, mostrem com l'esfera pública és un àmbit en el qual visions epistemològiques i de disciplina oposades competeixen pel domini discursiu en relació amb temes de llengua i societat, per autoritat institucional i per recursos. En lloc d'entendre la dialèctica entre els sociolingüistes amb l'esfera pública com una activitat desinteressada de disseminació de coneixement i de bases factuals, argumentem que l'esfera pública s'ha d'entendre com a terreny en el qual els sociolingüistes hi projecten expectatives institucionals, disciplinaries i professionals. En definitiva, l'article ajuda a entendre'ns com a sociolingüistes de manera més àmplia.